Baseline characteristics, analysis plan and report on feasibility for the Prevention Of Decline in Cognition After Stroke Trial (PODCAST) - Scutt, Polly; Blackburn, Dan; Krishnan, Kailash; Ballard, Clive; Burns, Alistair; Ford, Gary A.; Mant, Jonathan; Passmore, Peter; Pocock, Stuart; Reckless, John; Sprigg, Nikola; Stewart, Rob; et al. (BioMed Central, 2015)
Background